EFFECT OF TIMING AND RATIO OF UREA FERTILIZATION ON 15N RECOVERY AND YIELD OF COTTON - P.C. Li; A.Z. Liu; J.R. Liu; C.S. Zheng; M. Sun; G.P. Wang; Y; B. Li; X.H. Zhao; H.L. Dong (Journal of Animal and Plant Sciences, 2017)
Applications of urea before planting and at the initial flowering stage at ratios of 1:1 are the conventional nitrogen (N) fertilization method in the Yellow River Valley Cotton (Gossypium hirsutum L.) Area of China. This study was conducted to determine whether increasing urea fertilization ratios at the initial flowering stage or fertilization once at the budding or the initial flowering stage could improve seed cotton yield, plant 15N recovery, and decrease fertilizerN loss (FNL). Pot experiments were conducted in 2013 and 2014, arranged in a  randomized complete block design with two contemporary cultivars (CCRI 79 and CCRI 60), and four fertilization timing/ratios with the same total N application amount 3.5g N per 35 kg soil per pot over the entire growing stage, the conventional fertilization method (1:1), application of urea before planting and at the initial flowering stage at ratios of 1:2 and the application of urea all at the initial flowering stage and all at the budding stage.The results revealed that the application of urea all at the budding stage and all at the initial flowering stage could increase cotton plant 15N recovery and decrease the FNL compared to the split application of urea, and achieved similar seed cotton yield of conventional fertilization in addition to application of urea all at the budding stagefor CCRI 60in 2013. Application of urea before planting and at the initial flowering stage at ratios of 1:2 improved the seed cotton yields although could not significantly increase the cotton plant15N recovery and decreased the FNL comparing to the conventional fertilization method. It was feasible to decrease the N ratio of base N and increase the ratio of topdressing Nat the initial flowering stage based on conventional N fertilization method in cotton N management.
Keywords: urea; fertilization timing and ratio; seed cotton yield; 15N recovery; cotton